DIAGNOSTIC UTILITY OF PLEURAL FLUID ADENOSINE DEAMINASE LEVEL IN TUBERCULOUS PLEURAL EFFUSION - Suleman, Amir; Kamal, Muhammad; Abbasi, Munir Ahmad; Anwar, Syed Abbas; Khan, Haroon (Journal of Ayub Medical College Abbottabad, 2016)
Background: Early diagnosis and management of tuberculosis is essential for decreasing the disease burden. Pakistan is one of the few countries of world with a very high burden of tuberculosis. Many diagnostic tests are available for detection of tuberculosis but each is fraught with certain limitations of its own. Methods: This study was a cross sectional validation study that sought to determine the validity of pleural fluid adenosine deaminase levels for diagnosis of tuberculous pleural effusion. Results: A total of 160 patients with exudative lymphocytic pleural effusions were enrolled in this study. The mean pleural fluid ADA level was 52.18±1.98 U/L. The mean pleural fluid ADA level in patients diagnosed to have tuberculosis on pleural biopsy/histopathology was higher as compared to patients who did not have tuberculous pleural effusion 52.16±2.4 U/L vs 38.6±3.14 U/L. The difference was found to be statistically significant between the two groups (p<0.05). The sensitivity, specificity, ppv and npv of pleural fluid ADA level were 88.88%, 77.04%, 86.28% and 81.04% respectively. Conclusion: Despite wide variations in the reported sensitivity and specificity of pleural fluid ADA level, it can be used as a surrogate for pleural biopsy when the latter is not feasible. Keywords: Tuberculosis, tuberculous pleural effusion, adenosin deaminase, pleural biopsy